An effective partial fraction decomposition method for undergraduate students / Li Ling Jong ... [et al.] - Li, Ling Jong; Siaw, Vui Kuan (Universiti Teknologi MARA Cawangan Sarawak, 2020)
In order to propose a more effective alternative method employed by undergraduate students to compute the partial fraction decomposition (PFD) of rational functions which could eventually help to solve the prominent common errors made by undergraduate students during the computation using standard method, data from quizzes and questionnaires administered to 47 students were quantitatively analyzed. The findings of this study reveal that there is progress shown in students' performance when they apply the proposed alternative method, namely, the improved cover-up method. Students also appreciate the efficiency and accuracy of the alternative method offered. Hence, it is believed that this approach, which is considerably new to undergraduate students particularly in a public university in Sarawak, can serve as an alternative to the more conventional or standard method of undetermined coefficients used in teaching elementary integral calculus for better students' performance. Additionally, this preliminary evidence provides directions for future research related to partial fraction decomposition methods.